Separator for electrochemical device containing organic / inorganic composite porous coating layer and electrochemical device containing the same
The organic/inorganic composite porous coating layer in the separation film addresses adhesive force issues by using hybrid and acrylic polymer particles to maintain electrode cohesion in lithium secondary batteries, ensuring stability and performance in both dry and wet states.
Patent Information
- Application Number
- JP2024541067
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-04-24
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2043-04-24
AI Technical Summary
Existing electrochemical elements, such as lithium secondary batteries, face issues with adhesive force between the electrode and the separation film, particularly in dry and wet states, leading to potential separation during manufacturing and reduced battery performance due to insufficient cohesion and stability.
A separation film with an organic/inorganic composite porous coating layer containing hybrid polymer particles and acrylic polymer particles, where the hybrid polymer particles are insoluble to electrolytic solutions, maintaining adhesion in wet states, and acrylic polymer particles enhance adhesion in dry states, ensuring high durability and insulation.
The separation film maintains strong adhesion with electrodes in both dry and wet conditions, improving form stability and resistance to external stimuli, enhancing battery performance and safety by preventing separation and ensuring high cohesive force even when infiltrated by electrolytic solutions.
Smart Images

Figure 2025503630000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention claims the benefit of the filing dates of Korean Patent Application No. 10-2022-0054734, filed with the Korean Intellectual Property Office on May 3, 2022, and Korean Patent Application No. 10-2022-0061568, filed with the Korean Intellectual Property Office on May 19, 2022, each of which is incorporated in its entirety herein.
[0002] The present invention relates to a separator for an electrochemical device having improved adhesive strength in a dry state (dry adhesive strength) and adhesive strength when immersed in an electrolyte (wet adhesive strength). [Background technology]
[0003] Electrochemical devices such as lithium secondary batteries are generally composed of a positive electrode / separator / negative electrode / electrolyte, and are high-energy density energy storage devices that can be charged and discharged while reversibly converting chemical energy and electrical energy, and are widely used in small electronic devices such as mobile phones and laptops. In recent years, in response to environmental issues, high crude oil prices, and energy efficiency and storage, their application to hybrid electric vehicles (HEVs), plug-in EVs, electric bicycles (e-bikes), and energy storage systems (ESSs) has been rapidly expanding.
[0004] Ensuring the safety of such lithium secondary batteries in their manufacture and use is an important issue. In particular, separators commonly used in electrochemical devices exhibit extreme thermal shrinkage behavior at high temperatures due to their material properties and manufacturing process properties, resulting in stability problems such as internal short circuits. Recently, in order to ensure the safety of lithium secondary batteries, an organic / inorganic composite porous separator has been proposed in which a mixture of inorganic particles and a binder resin is coated on a porous polymer substrate to form an organic / inorganic composite porous coating layer. However, when an electrode and a separator are laminated to form an electrode assembly, there is a high risk that the electrode and the separator will be separated from each other due to insufficient interlayer adhesion, and in this case, there is a problem that inorganic particles detached during the separation process may act as local defects in the device. In order to improve the adhesion between the electrode and the separator, a separator in which an acrylic polymer binder is applied to an organic / inorganic composite porous coating layer has been proposed. However, although the dry adhesion is improved when an acrylic polymer binder is used, there is a problem that the wet adhesion is reduced after application to a battery due to problems such as the acrylic polymer binder swelling or dissolution by the electrolyte.
[0005] As such, there is a need to develop a separator that maintains a high adhesive strength from the time of manufacturing the separator including the organic / inorganic composite porous coating layer until it is applied to a battery. Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an organic / inorganic composite porous separator having improved adhesion to an electrode both in a dry state and in a wet state.
[0007] Another object of the present invention is to provide a separator that maintains high durability and insulating properties without causing inorganic particles to fall off from the organic / inorganic composite porous coating layer.
[0008] Other objects and advantages of the present invention will become apparent from the following description. Meanwhile, it will be easily understood that the objects and advantages of the present invention can be realized by the means or methods recited in the claims, and combinations thereof. [Means for solving the problem]
[0009] A first aspect of the present invention relates to a separator for an electrochemical device, comprising: a porous polymer substrate; and an organic / inorganic composite porous coating layer formed on at least one side of the polymer substrate, The organic / inorganic composite porous coating layer includes a particulate binder resin and inorganic particles, The particulate binder polymer includes hybrid polymer particles of a fluorine-based polymer and an acrylic polymer, and acrylic polymer particles, The acrylic polymer constituting the hybrid polymer particles does not contain a styrene-based repeating unit, and the acrylic polymer constituting the acrylic polymer particles contains a styrene-based repeating unit, The organic / inorganic composite porous coating layer has a heterogeneity of composition morphology in a thickness direction, in which a content ratio of hybrid polymer particles / acrylic polymer particles present on a surface portion opposite to a surface in contact with the polymer substrate is greater than a content ratio of hybrid polymer particles / acrylic polymer particles present inside the organic / inorganic composite porous coating layer.
[0010] In a second aspect of the present invention, in the first aspect, the organic / inorganic composite porous coating layer has a heterogeneity in composition morphology in a thickness direction, in which a content of hybrid polymer particles present in a surface portion opposite to a surface in contact with the polymer substrate is greater than a content of hybrid polymer particles present inside the organic / inorganic composite porous coating layer.
[0011] In a third aspect of the present invention, in the second aspect, the organic / inorganic composite porous coating layer has a heterogeneity in composition morphology in a thickness direction, in which a content of acrylic polymer particles present in a surface portion opposite to a surface in contact with the polymer substrate is greater than a content of acrylic polymer particles present inside the organic / inorganic composite porous coating layer.
[0012] In a fourth aspect of the present invention, in any one of the first to third aspects, the average particle size (D50) of the hybrid polymer particles is smaller than the average particle size (D50) of the acrylic polymer particles.
[0013] A fifth aspect of the present invention is the fourth aspect, wherein the hybrid polymer particles have an average particle size (D50) of 100 nm to 500 nm, and the acrylic polymer particles have an average particle size (D50) of 200 nm to 700 nm, more specifically, the hybrid polymer particles have an average particle size (D50) of 200 nm to 400 nm, and the acrylic polymer particles have an average particle size (D50) of 300 nm to 500 nm.
[0014] In a sixth aspect of the present invention, in any one of the first to fifth aspects, a mixing weight ratio of the hybrid polymer particles to the acrylic polymer particles is 8:2 to 2:8.
[0015] A seventh aspect of the present invention is any one of the first to sixth aspects, wherein the Tg of the acrylic polymer contained in the hybrid polymer particles is lower by 10°C or more than the Tg of the acrylic polymer contained in the acrylic polymer particles, more specifically, the Tg of the acrylic polymer contained in the hybrid polymer particles is 10°C to 30°C, and the Tg of the acrylic polymer contained in the acrylic polymer particles is 30°C to 50°C.
[0016] An eighth aspect of the present invention is any one of the first to seventh aspects, wherein the fluorine-based polymer is a homopolymer of vinylidene fluoride, a copolymer of vinylidene fluoride and another polymerizable monomer, or a mixture of two or more of these.
[0017] A ninth aspect of the present invention is any one of the first to eighth aspects, wherein the monomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2 difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3 dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride.
[0018] A tenth aspect of the present invention is any one of the first to ninth aspects, wherein the fluorine-based polymer is a copolymer of vinylidene fluoride and hexafluoropropylene.
[0019] An eleventh aspect of the present invention is any one of the first to tenth aspects, wherein the content of the monomer is 1% by weight to 20% by weight of the copolymer.
[0020] A twelfth aspect of the present invention is any one of the first to eleventh aspects, wherein the acrylic polymer constituting the hybrid polymer particles and the acrylic polymer constituting the acrylic polymer particles each independently contain an alkyl (meth)acrylate repeating unit having an alkyl group having 1 to 18 carbon atoms.
[0021] A thirteenth aspect of the present invention is any one of the first to twelfth aspects, wherein the organic / inorganic composite porous coating layer contains the particulate binder resin in a range of 1 wt % to 30 wt % of the organic / inorganic composite porous coating layer.
[0022] In a fourteenth aspect of the present invention, in any one of the first to thirteenth aspects, the inorganic particles have an average particle size (D50) in the range of 200 nm to 3 μm.
[0023] A fifteenth aspect of the present invention is any one of the first to fourteenth aspects, wherein the organic / inorganic composite porous coating layer is formed by coating a slurry in which the particulate binder resin and inorganic particles are dispersed in an aqueous dispersion medium onto at least one surface of a porous polymer substrate and drying the slurry.
[0024] A sixteenth aspect of the present invention relates to an electrochemical element, the electrochemical element comprising a negative electrode, a positive electrode, and a separation membrane interposed between the negative electrode and the positive electrode, the separation membrane being related to any one of the first to fourteenth aspects.
[0025] A seventeenth aspect of the present invention is the sixteenth aspect, wherein the electrochemical device is a lithium secondary battery. Effect of the Invention
[0026] The organic / inorganic composite porous coating layer of the separation membrane according to the present invention simultaneously contains hybrid polymer particles of a fluorine-based polymer and an acrylic polymer, and acrylic polymer particles, and has heterogeneity in composition morphology in the thickness direction, in which the content ratio of the hybrid polymer particles / acrylic polymer particles present on the surface portion opposite to the surface in contact with the polymer substrate is greater than the content ratio of the hybrid polymer particles / acrylic polymer particles present inside the organic / inorganic composite porous coating layer.
[0027] According to the present invention, the content ratio of hybrid polymer particles / acrylic polymer particles present on the surface of the organic / inorganic composite porous coating layer opposite to the surface in contact with the polymer substrate is greater than the content ratio of hybrid polymer particles / acrylic polymer particles present inside the organic / inorganic composite porous coating layer. Since the fluoropolymer contained in the hybrid polymer particles is insoluble in the electrolyte, even if the hybrid polymer particles simultaneously contain an acrylic polymer, the hybrid polymer particles maintain their shape even when wet with the electrolyte. As a result, the separator of the present invention maintains its adhesion to the electrode without significantly impairing the adhesion to the electrode even in a wet state. Meanwhile, the acrylic polymer particles further contribute to maintaining the adhesion of the separator to the electrode in a dry state.
[0028] Therefore, in a roll-to-roll continuous process for manufacturing an electrode assembly by stacking an electrode and the separator of the present invention, the shape stability and processability of the electrode assembly are improved. In addition, when a battery is manufactured using an electrode assembly including the separator, a high binding strength can be maintained between the separator and the electrode even when the separator is immersed in an electrolyte, so that the interfacial resistance characteristics are not deteriorated. In addition, since the binder resin particles maintain a high adhesive strength in a dry state or a wet state, the inorganic particles contained in the organic / inorganic composite porous coating layer are well fixed without being detached, so that the shape stability of the separator can be improved. Therefore, the heat resistance safety and insulation properties of the battery are improved.
[0029] Furthermore, the acrylic polymer constituting the hybrid polymer particles does not contain a styrene-based repeating unit, and the acrylic polymer constituting the acrylic polymer particles contains a styrene-based repeating unit, thereby improving the adhesive strength between the porous polymer substrate and the organic / inorganic composite porous coating layer. [Brief description of the drawings]
[0030] The accompanying drawings illustrate preferred embodiments of the invention and, together with the detailed description, are intended to explain the principles of the invention, and are not intended to limit the scope of the invention. Meanwhile, the shape, size, scale, ratio, etc. of elements in the drawings described in this specification may be exaggerated in order to emphasize a clearer description.
[0031] [Figure 1] FIG. 1 is a schematic cross-sectional view of a separation membrane according to a specific embodiment of the present invention. [Figure 2a] FIG. 2a shows an SEM image of the surface of the separation membrane of Example 1 before impregnation with the electrolyte. [Figure 2b] FIG. 2b is an enlarged partial view of FIG. 2a. [Figure 3a] FIG. 3a shows an SEM image of the surface of the separation membrane of Comparative Example 1. [Figure 3b] FIG. 3b is an enlarged partial view of FIG. 3a. [Figure 4] FIG. 4 is an SEM image of a cross section of the separation membrane according to Example 1. As shown in FIG. [Diagram 5] FIG. 5 is an EDS image of a cross section of the separation membrane according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] The terms or words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as being consistent with the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention. Therefore, it should be understood that the embodiments described in the present specification and the configurations illustrated in the drawings are merely the most preferred embodiments of the present invention, and do not represent the entire technical idea of the present invention, and therefore there may be various equivalents and modifications that can replace them at the time of filing this application.
[0033] FIG. 1 is a schematic cross-sectional view of a separator for an electrochemical device (10) according to one specific embodiment of the present invention.
[0034] In the present invention, the separation membrane 10 includes a porous polymer substrate 1 and an organic / inorganic composite porous coating layer 3 formed on at least one surface of the polymer substrate 1. Although Fig. 1 illustrates that the organic / inorganic composite porous coating layer 3 is formed on only one surface of the polymer substrate 1, it is of course possible for the organic / inorganic composite porous coating layer 3 to be formed on the other surface of the polymer substrate 1.
[0035] The organic / inorganic composite porous coating layer (3) contains particulate binder resins (5, 7) and inorganic particles (9). The particulate binder polymers (5, 7) contain hybrid polymer particles (5) of a fluorine-based polymer and an acrylic polymer, and acrylic polymer particles (7).
[0036] In the present invention, the acrylic polymer constituting the hybrid polymer particles does not contain a styrene repeating unit, and the acrylic polymer constituting the acrylic polymer particles contains a styrene repeating unit. Specifically, in the process of polymerizing the acrylic polymer constituting the hybrid polymer particles, a styrene compound, a copolymer containing a styrene repeating unit, or a polymer containing a styrene repeating unit, which is a monomer, is not contained, which means that a styrene repeating unit is not contained, and in the process of polymerizing the acrylic polymer constituting the acrylic polymer particles, a styrene compound, a copolymer containing a styrene repeating unit, or a polymer containing a styrene repeating unit is contained, which means that a styrene repeating unit is contained.
[0037] As shown in FIG. 1, the organic / inorganic composite porous coating layer (3) has a heterogeneity in composition morphology in the thickness direction, in which the content ratio of hybrid polymer particles (5) / acrylic polymer particles (7) present on the surface portion opposite the surface in contact with the polymer substrate (1) is greater than the content ratio of hybrid polymer particles (5) / acrylic polymer particles (7) present inside the organic / inorganic composite porous coating layer (3).
[0038] In the present specification, "heterogeneity of composition morphology in the thickness direction, in which the content ratio of hybrid polymer particles / acrylic polymer particles present in the surface portion of the organic / inorganic composite porous coating layer opposite to the surface in contact with the polymer substrate is greater than the content ratio of hybrid polymer particles / acrylic polymer particles present inside the organic / inorganic composite porous coating layer" should be interpreted as including any embodiment as long as the content ratio of hybrid polymer particles / acrylic polymer particles present in the surface portion of the organic / inorganic composite porous coating layer opposite to the surface in contact with the polymer substrate is greater than the content ratio of hybrid polymer particles / acrylic polymer particles present under (inside) the surface portion of the porous coating layer. For example, it should be construed as including all of a porous coating layer formed such that the content ratio of hybrid polymer particles / acrylic polymer particles decreases linearly from the surface of the porous coating layer toward the porous substrate, a porous coating layer formed such that the content ratio of hybrid polymer particles / acrylic polymer particles decreases nonlinearly from the surface of the porous coating layer toward the porous substrate, and a porous active layer formed such that the content ratio of hybrid polymer particles / acrylic polymer particles decreases discontinuously from the surface of the porous coating layer toward the porous substrate.
[0039] Thus, the content ratio of the hybrid polymer particles / acrylic polymer particles present on the surface of the organic / inorganic composite porous coating layer opposite to the surface in contact with the polymer substrate is greater than the content ratio of the hybrid polymer particles / acrylic polymer particles present inside the organic / inorganic composite porous coating layer. Since the fluoropolymer contained in the hybrid polymer particles is insoluble in the electrolyte, the hybrid polymer particles maintain their shape even when wet with the electrolyte, even if they simultaneously contain an acrylic polymer. As a result, the separator of the present invention maintains its adhesion to the electrode without significantly impairing its adhesion to the electrode even in a wet state. Meanwhile, the acrylic polymer particles further contribute to maintaining the adhesion of the separator to the electrode in a dry state.
[0040] The organic / inorganic composite porous coating layer (3) may have a heterogeneity of composition morphology in the thickness direction in which the content of the hybrid polymer particles (5) present on the surface portion opposite to the surface in contact with the polymer substrate (1) is greater than the content of the hybrid polymer particles (5) present inside the organic / inorganic composite porous coating layer (3). Also, the organic / inorganic composite porous coating layer (3) may have a heterogeneity of composition morphology in the thickness direction in which the content of the acrylic polymer particles (7) present on the surface portion opposite to the surface in contact with the polymer substrate (1) is greater than the content of the acrylic polymer particles (7) present inside the organic / inorganic composite porous coating layer (3).
[0041] In this way, when the hybrid polymer particles (5) and / or the acrylic polymer particles (7) have the above-mentioned composition morphology heterogeneity in the thickness direction, the polymer particles (5, 7) are present in greater numbers on the surface opposite to the surface in contact with the polymer substrate (1) than in the interior of the organic / inorganic composite porous coating layer (3). Therefore, the adhesive properties of the polymer particles present in greater numbers on the surface increase the dry / wet adhesive strength to the electrode. In addition, the resistance to external stimuli such as peeling and scratching increases, improving the lamination properties to the electrode. As a result, the battery can exhibit excellent properties in the battery assembly process such as winding and lamination. In addition, the inorganic particles, which increase in number toward the interior, improve the porosity, thereby exhibiting excellent ion conductivity properties and contributing to improved battery performance.
[0042] According to a specific embodiment of the present invention, the porous polymer substrate (1) can provide a lithium ion migration path while electrically insulating the negative and positive electrodes to prevent short circuits, and can be used without any particular limitation as long as it is generally usable as a separator polymer substrate for an electrochemical device. As such a separator substrate, for example, a porous polymer film or nonwoven fabric containing one or more polymer resins such as polyolefins such as polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene can be used.
[0043] In the present invention, the thickness of the polymer substrate may be 3 μm to 50 μm. The range of the separator substrate is not particularly limited to the above range, but if the thickness is less than the above lower limit, the mechanical properties may be deteriorated and the separator may be easily damaged during use of the battery. Meanwhile, the pore size and porosity of the separator substrate are not particularly limited, but may be 0.01 μm to 50 μm and 10 vol% to 95 vol%, respectively.
[0044] The organic / inorganic composite porous coating layer (3) is formed by mixing a plurality of inorganic particles (9) and particulate binder resins (5, 7). The polymer substrate (1) is coated with the porous coating layer (3) containing the inorganic particles (9), so that the heat resistance and mechanical properties of the separator (10) can be further improved. According to a preferred embodiment of the present invention, the organic / inorganic composite porous coating layer (3) is disposed on both sides of the polymer substrate (1). As such, the porous coating layer (3) is formed on both sides of the porous substrate (1), so that the wet adhesive strength and dry adhesive strength between the positive electrode and the separator and between the negative electrode and the separator can be improved.
[0045] The organic / inorganic composite porous coating layer (3) may have a microporous structure due to an interstitial volume between the inorganic particles (9) and the particulate binder polymers (5, 7) constituting the organic / inorganic composite porous coating layer (3). The inorganic particles (9) also act as a kind of spacer capable of maintaining the physical form of the porous coating layer (3). The interstitial volume means a space defined by the substantial surface contact between the inorganic particles (9) and the particulate binder polymers (5, 7). In addition, the inorganic particles (9) generally have a property that their physical properties do not change even at high temperatures of 200°C or more, so that the organic / inorganic composite porous coating layer (3) provides the separator (10) with excellent heat resistance. In the present invention, the organic / inorganic composite porous coating layer (3) may have a thickness in the range of 1 μm to 50 μm, or 2 μm to 30 μm, or 2 μm to 20 μm, based on the thickness formed on any one surface of the porous substrate (1).
[0046] In the present invention, the particulate binder polymer (5, 7) is a binder polymer that maintains the particle shape added by being added in particulate form to a dispersion medium during the formation of the porous coating layer (3) and then coated and dried, and is distinguished from a non-particulate binder polymer that is coated and dried in a form dissolved in a solvent.
[0047] In one embodiment of the present invention, the particulate binder polymer (5, 7) may account for 90% by weight or more or 99% by weight or more of the binder components present in the porous coating layer (3). In this specification, the particulate binder polymer (5, 7) may be referred to as polymer particles, resin particles, binder particles, etc. The particulate binder polymer (5, 7) forms a layered porous coating layer (3) by bonding the inorganic particles (9) to each other and bonding the inorganic particles (9) to the polymer substrate (1).
[0048] In the present invention, the average particle size (D50) of the hybrid polymer particles may be smaller than the average particle size (D50) of the acrylic polymer particles. By making the average particle size (D50) of the hybrid polymer particles smaller than the average particle size (D50) of the acrylic polymer particles, it is possible to more easily form an organic / inorganic composite porous coating layer having heterogeneity in composition morphology in the thickness direction.
[0049] In one embodiment of the present invention, the hybrid polymer particles have an average particle size (D50) of 100 nm to 500 nm, the acrylic polymer particles have an average particle size (D50) of 200 nm to 700 nm, more specifically, the hybrid polymer particles have an average particle size (D50) of 200 nm to 400 nm, and the acrylic polymer particles have an average particle size (D50) of 300 nm to 500 nm. Also, the mixing weight ratio of the hybrid polymer particles to the acrylic polymer particles may be 8:2 to 2:8.
[0050] Hybrid polymeric particles can be prepared, for example, by reference to WO 2020 / 263936, which is incorporated herein by reference.
[0051] The fluorine-based polymer contained in the hybrid polymer particles is insoluble in the electrolyte and may be a homopolymer of vinylidene fluoride, a copolymer of vinylidene fluoride and another polymerizable monomer, or a mixture of two or more of these.
[0052] Examples of the vinylidene fluoride and other polymerizable monomers include, but are not limited to, at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2 difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3 dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride. In particular, the fluorine-based polymer may be a copolymer of vinylidene fluoride and hexafluoropropylene. The content of vinylidene fluoride and other polymerizable monomers may be, but is not limited to, 1 to 20% by weight of the copolymer.
[0053] In the present invention, the content of the comonomer in the PVDF-based polymer can be measured by 1H-NMR using Varian 500MHz. For details of the measurement method, refer to Journal of Materials Chemistry, 2012, 22, 341 or AMT-3412-0k. For confirmation of the NMR spectrum, a suitable device such as Bruker Avance III HD 700Mhz NMR or Varian 500MHz NMR can be used.
[0054] The acrylic polymer constituting the hybrid polymer particles and the acrylic polymer constituting the acrylic polymer particles may each independently contain an alkyl (meth)acrylate repeating unit having an alkyl group having a carbon number of 1 to 18, but are not limited thereto. However, the acrylic polymer constituting the hybrid polymer particles does not contain a styrene-based repeating unit, and the acrylic polymer constituting the acrylic polymer particles contains a styrene-based repeating unit.
[0055] In one embodiment of the present invention, the Tg of the acrylic polymer contained in the hybrid polymer particles may be lower than the Tg of the acrylic polymer contained in the acrylic polymer particles by at least 10° C. Since the lower the Tg of the acrylic polymer, the more advantageous it is for improving adhesive strength, the dry / wet adhesive strength of the hybrid polymer particles to the electrodes can be further improved by selecting an acrylic polymer having a low Tg for the hybrid polymer particles.
[0056] More specifically, the Tg of the acrylic polymer contained in the hybrid polymer particles may be 10° C. to 30° C., and the Tg of the acrylic polymer contained in the acrylic polymer particles may be 30° C. to 50° C. Even if the acrylic polymer contained in the hybrid polymer particles has a low Tg, it can maintain a particulate shape even at room temperature due to the hybridized fluorine-based polymer. In addition, when the acrylic polymer contained in the acrylic polymer particles is selected to have a Tg of at least room temperature, it can maintain a particulate shape at room temperature and exhibit electrode adhesive strength during lamination with an electrode.
[0057] The acrylic polymer may have a glass transition temperature (Tg) of 40° C. or less.
[0058] More specifically, the acrylic polymer may be a polymer containing a carboxylate ester as a repeating unit, and may preferably be a (meth)acrylic ester. Specific examples of such (meth)acrylic esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-amyl (meth)acrylate, i-amyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and (meth)acrylic ester. Examples of the acrylate include decyl (meth)acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, ethylene glycol (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, and ethylene di(meth)acrylate, and may be one or more selected from these. Among these, the acrylate may be one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, and is particularly preferably methyl (meth)acrylate.
[0059] The organic / inorganic composite porous coating layer may contain the particulate binder resin in an amount ranging from 1% by weight to 30% by weight of the organic / inorganic composite porous coating layer, but is not limited thereto.
[0060] The inorganic particles contained in the organic / inorganic composite porous coating layer are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles are preferably within the operating voltage range (e.g., Li / Li +There are no particular limitations as long as oxidation and / or reduction reactions do not occur at a potential of 0 to 5 V relative to the reference potential. In particular, when inorganic particles having ion transfer ability are used, the ion conductivity in the electrochemical element can be increased to improve performance. In addition, when inorganic particles having a high dielectric constant are used as the inorganic particles, they can contribute to an increase in the degree of dissociation of the electrolyte salt in the liquid electrolyte, for example, the lithium salt, thereby improving the ion conductivity of the electrolyte solution.
[0061] For the reasons mentioned above, the inorganic particles may include high dielectric constant inorganic particles having a dielectric constant of 5 or more, or 10 or more, inorganic particles having lithium ion transfer ability, or a mixture thereof. Non-limiting examples of inorganic particles having a dielectric constant of 5 or more include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT, where 0 <x<1、0<y<1である)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, SiC, TiO2, etc. can be used alone or in combination of two or more. In addition, when the above-mentioned high dielectric constant inorganic particles are mixed with inorganic particles having lithium ion transfer ability, the synergistic effect of these can be doubled.
[0062] Non-limiting examples of the inorganic particles having lithium ion transport ability include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 <x<2、0<y<3)、リチウムアルミニウムチタンホスフェート(Li x Al y Ti z (PO4)3, 0 <x<2、0<y<1、0<z<3)、14Li2O-9Al2O3-38TiO2-39P2O5などといった(LiAlTiP) x O ySystem glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), Li 3.25 Ge 0.25 P 0.75 S4, etc., such as lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride such as Li3N (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glass such as Li3PO4-Li2S-SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5-based glass such as LiI-Li2S-P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7) or mixtures thereof, etc.
[0063] In the organic / inorganic composite porous coating layer, the content ratio of the inorganic particles is determined in consideration of the thickness, pore size, and porosity of the finally manufactured organic / inorganic composite porous coating layer, but based on the weight ratio, the inorganic particles can be contained in the range of 70% to 99% by weight with respect to 100% by weight of the porous coating layer. If the content of the inorganic particles is less than 70% by weight, the heat resistance may decrease. On the other hand, if the content of the inorganic particles is too high, the amount of the binder is too small, so the adhesion of the porous coating layer may decrease.
[0064] According to a specific embodiment of the present invention, the inorganic particle size of the organic / inorganic composite porous coating layer is not limited, but may be in the range of 0.001 μm to 10 μm as much as possible in order to form a coating layer of uniform thickness and appropriate porosity. For example, the inorganic particle size is 200 nm to 3 μm, 200 nm to 2 μm, or 200 nm to 1 μm within the above range. When the inorganic particle size satisfies this range, the dispersibility is maintained, making it easy to control the physical properties of the separator, and the increase in the thickness of the organic / inorganic composite porous coating layer can be prevented, improving the mechanical properties, and reducing the possibility of an internal short circuit occurring during charging and discharging of the battery due to an excessively large pore size.
[0065] Meanwhile, in one embodiment of the present invention, the separator including the organic / inorganic composite porous coating layer may be prepared by mixing binder particles and inorganic particles with an aqueous dispersion medium to prepare a slurry for forming a coating layer, and then coating the slurry on at least one side of a polymer substrate.
[0066] The coating method may be dip coating, die coating, roll coating, comma coating, or a mixture thereof.
[0067] In one embodiment of the present invention, the aqueous dispersion medium may include one or more of water and alcohols having 1 to 5 carbon atoms. For example, the aqueous dispersion medium may include a mixture of water and isopropyl alcohol. By using an aqueous dispersion medium in the preparation method, the binder particles are not dissolved in the dispersion medium and are dispersed in the aqueous dispersion medium while maintaining their particle shape. For this reason, the binder particles can maintain a particle state in the prepared organic / inorganic composite porous coating layer and do not flow into the pores of the polymer substrate.
[0068] Meanwhile, in one embodiment of the present invention, the slurry for forming the coating layer is preferably controlled so that the solid content concentration excluding the dispersion medium is in the range of 20wt% to 50wt%. It is advantageous to obtain a separator having an organic / inorganic composite porous coating layer having heterogeneity of composition morphology according to the present invention by controlling the solid content concentration, the average particle size and the content ratio of the binder particles to be added within the above-mentioned ranges.
[0069] Meanwhile, in the present invention, the separator may be applied to an electrochemical device. The electrochemical device may include an anode and a cathode, and the separator may be interposed between the anode and the cathode. The electrochemical device may include any device that performs an electrochemical reaction, and specific examples thereof include any type of primary battery, secondary battery, fuel cell, solar cell, or capacitor. In particular, among the secondary batteries, lithium ion secondary batteries, including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, or lithium ion polymer secondary batteries, are preferred.
[0070] In one embodiment of the present invention, the electrochemical device may be manufactured according to a conventional method known in the art. According to one embodiment of the present invention, the electrochemical device may be configured by interposing the above-mentioned separator between the positive electrode and the negative electrode. In addition, the electrochemical device may be manufactured by inserting an electrode assembly, in which the negative electrode, the separator, and the positive electrode are stacked, into a battery case and then injecting an electrolyte solution.
[0071] In one embodiment of the present invention, the electrode is not particularly limited, and the electrode active material may be prepared in a form bonded to an electrode current collector according to a conventional method known in the art. Among the electrode active materials, non-limiting examples of the positive electrode active material include conventional positive electrode active materials that can be used in the positive electrode of conventional electrochemical devices, and in particular, lithium intercalation materials such as lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a composite oxide formed by a combination thereof are preferred. Non-limiting examples of the negative electrode active material include conventional negative electrode active materials that can be used in the negative electrode of conventional electrochemical devices, and in particular, lithium intercalation materials such as lithium metal or lithium alloy, carbon, petroleum coke, activated carbon, graphite, or other carbons are preferred. Non-limiting examples of positive current collectors include foils made of aluminum, nickel, or combinations thereof, and non-limiting examples of negative current collectors include foils made of copper, gold, nickel, or copper alloys, or combinations thereof.
[0072] The electrolyte that can be used in the present invention is A + B - A salt having the structure: + Li + , Na + , K + or a combination thereof, - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 -or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof.
[0073] The electrolyte injection may be performed at an appropriate stage during the battery manufacturing process depending on the manufacturing process and required properties of the final product, i.e., before the battery assembly or at the final stage of the battery assembly. In addition to the general winding process, lamination (stack) and folding processes of the separator and the electrodes are also possible processes for applying the electrode assembly of the present invention to a battery.
[0074] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention may be modified in various different forms, and the scope of the present invention should not be construed as being limited to the examples detailed below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.
[0075] Working Example Example 1 8.2 parts by weight of hybrid polymer particles [D50: 300 nm, hybrid polymer particles in which a copolymer of VDF and HFP polymerized at a molar ratio of 95:5 and a copolymer of ethyl acrylate and methyl methacrylate (Tg 20°C) are mixed at a weight ratio of 7:3], 8.2 parts by weight of acrylic polymer particles [D50: 400 nm, copolymer of styrene and butyl acrylate (Tg 40°C)], and 80 parts by weight of inorganic particles (Al2O3, D50: 500 nm) were added and dispersed in water to prepare a dispersion liquid (solid concentration 35% by weight) for forming a porous coating layer.
[0076] Next, a polyethylene membrane substrate (porosity 40%, thickness 9 μm) was prepared, and the dispersion was applied to both sides of the surface of the membrane substrate by a bar coating method using a doctor blade, and then dried with hot air at 50° C. using a heat gun to form a porous coating layer having a thickness of 12 μm on one side.
[0077] Figure 4 is an SEM image of a cross section of the separation membrane according to Example 1, and Figure 5 is an EDS image of a cross section of the separation membrane according to Example 1. Referring to Figure 5, the distribution of the hybrid polymer particles contained in the organic / inorganic composite porous coating layer can be confirmed from an image related to F Kα1,2, which is obtained by analyzing the distribution of element F contained in the hybrid polymer particles. Meanwhile, the distribution of the acrylic polymer particles can be confirmed from an image related to Ru Lα1, which is obtained by analyzing the distribution of element Ru after staining with RuO4.
[0078] Example 2 A porous coating layer was formed in the same manner as in Example 1, except that the content of the hybrid polymer particles was changed to 10.2 parts by weight, the content of the acrylic polymer particles was changed to 10.2 parts by weight, and the content of the inorganic particles was changed to 75 parts by weight to prepare a dispersion for forming a porous coating layer (solid concentration: 35% by weight).
[0079] Comparative Example 1 A porous coating layer was formed in the same manner as in Example 1, except that the hybrid polymer particles were not added and the content of the acrylic polymer particles was changed to 16.4 parts by weight to prepare a dispersion for forming a porous coating layer (solid concentration: 35% by weight).
[0080] Comparative Example 2 A porous coating layer was formed in the same manner as in Example 1, except that the acrylic polymer particles were not added and the content of the hybrid polymer particles was changed to 16.4 parts by weight to prepare a dispersion for forming a porous coating layer (solid concentration: 35% by weight).
[0081] Comparative Example 3 A porous coating layer was formed in the same manner as in Example 1, except that the copolymer of ethyl acrylate and methyl methacrylate in the hybrid polymer particles was changed to a copolymer of styrene and butyl methacrylate to prepare a dispersion for forming a porous coating layer (solid concentration: 35 wt%).
[0082] Comparative Example 4 A porous coating layer was formed in the same manner as in Example 1, except that the acrylic polymer particles were changed from a copolymer of styrene and butyl acrylate to a copolymer of butyl acrylate to prepare a dispersion for forming a porous coating layer (solid concentration 35 wt%).
[0083] Comparative Example 5 A porous coating layer was formed in the same manner as in Example 1, except that the copolymer of ethyl acrylate and methyl methacrylate in the hybrid polymer particles was changed to a copolymer of styrene and butyl methacrylate, and the copolymer of styrene and butyl acrylate in the acrylic polymer particles was changed to a copolymer of butyl acrylate to prepare a dispersion for forming a porous coating layer (solid concentration 35 wt%).
[0084] Measurement of average particle size D50 D50 may be defined as the particle size at 50% of the particle size distribution, measured using the laser diffraction method.
[0085] Measurement of Tg Using DSC, Tg of a 25 mg sample was measured under conditions of a nitrogen atmosphere, room temperature to 300°C, and a heating rate of 10°C / min.
[0086] [Preparation of wet adhesion test pieces] The separator and the positive electrode obtained in each Example and Comparative Example were laminated, impregnated with 1.0 g of the electrolyte (ethylene carbonate: ethyl methyl carbonate = 7: 3, content ratio, LiPF61M), and left at room temperature for 24 hours. After that, a test piece was prepared by lamination using a hot press. At this time, pressure was applied at 70 ° C and 5 kgf for 5 minutes. The size of the test piece was 2 cm × 6 cm.
[0087] The positive electrode was prepared as follows: LiNi 0.8 Co 0.1 Mn 0.1 O2, PVDF and carbon black were mixed in a weight ratio of 97.0:1.5:1.5 and dispersed in 2-methyl-2-pyrrolidone to prepare a positive electrode slurry, which was then coated on an aluminum current collector, dried and rolled to prepare a positive electrode.
[0088] [Preparation of dry adhesive strength test pieces] The separator and the negative electrode obtained in each Example and Comparative Example were stacked and laminated using a hot press to prepare a test piece. At this time, pressure was applied at 60° C. and 6.5 MPa for 1 second. The size of the test piece was 2 cm × 6 cm.
[0089] The negative electrode was prepared as follows: Graphite, SBR, and CMC were mixed in a weight ratio of 89.2:10:0.8, and dispersed in distilled water to prepare a negative electrode slurry, which was then coated onto a copper current collector, dried, and rolled to prepare a negative electrode.
[0090] [Measurement of Adhesion Strength with Electrode] The wet adhesion and dry adhesion of the separator were evaluated using each test piece prepared as above, and the results are summarized in Table 1 below. Each test piece was prepared and left at room temperature for 1 hour, and then the adhesion was measured. The adhesion was measured using a tensile tester (UTM device) by peeling at an angle of 180° for dry adhesion and 90° for wet adhesion.
[0091] [Table 1]
[0092] As can be seen from Table 1, the separator according to the present invention was found to have good wet adhesion and dry adhesion to the electrodes. In the case of Comparative Example 1, the dry adhesion was high, but the wet adhesion was low, so that the battery performance may be deteriorated when actually applied to a battery. In Comparative Example 2, the dry adhesion was low, so that the adhesion was reduced during the manufacturing process of the electrode assembly. Furthermore, in Comparative Examples 3 to 5, the wet adhesion and dry adhesion were all low, so that the adhesion was reduced during the manufacturing process of the electrode assembly, so that the battery performance may be deteriorated when actually applied to a battery. However, the separator according to the Examples exhibited high wet adhesion and dry adhesion, so that it could exhibit excellent electrochemical effects during the manufacturing process of the electrode assembly and during the operation of the battery. [Explanation of symbols]
[0093] 1: Porous base material 3: Organic / inorganic composite porous coating layer 5: Hybrid polymer particles 7: Acrylic polymer particles 9: Inorganic particles 10: Separation membrane
Claims
1. The present invention includes a porous polymer substrate and an organic / inorganic composite porous coating layer formed on at least one side of the polymer substrate, The organic / inorganic composite porous coating layer includes a particulate binder resin and inorganic particles, The particulate binder polymer includes hybrid polymer particles of a fluorine-based polymer and an acrylic polymer, and acrylic polymer particles, The acrylic polymer constituting the hybrid polymer particles does not contain a styrene-based repeating unit, and the acrylic polymer constituting the acrylic polymer particles contains a styrene-based repeating unit, The organic / inorganic composite porous coating layer has a heterogeneity of composition morphology in a thickness direction, in which a content ratio of hybrid polymer particles / acrylic polymer particles present on a surface portion opposite to a surface contacting the polymer substrate is greater than a content ratio of hybrid polymer particles / acrylic polymer particles present inside the organic / inorganic composite porous coating layer.
2. 2. The separator for an electrochemical device according to claim 1, wherein the organic / inorganic composite porous coating layer has a heterogeneity in composition morphology in a thickness direction, in which a content of hybrid polymer particles present in a surface portion opposite to a surface in contact with the polymer substrate is greater than a content of hybrid polymer particles present inside the organic / inorganic composite porous coating layer.
3. 2. The separator for an electrochemical device according to claim 1, wherein the organic / inorganic composite porous coating layer has a heterogeneity in composition morphology in a thickness direction, in which a content of acrylic polymer particles present in a surface portion opposite to a surface in contact with the polymer substrate is greater than a content of acrylic polymer particles present inside the organic / inorganic composite porous coating layer.
4. 2. The separator for an electrochemical device according to claim 1, wherein the hybrid polymer particles have an average particle size (D50) smaller than the average particle size (D50) of the acrylic polymer particles.
5. 5. The separator for electrochemical devices according to claim 4, wherein the hybrid polymer particles have an average particle size (D50) of 100 nm to 500 nm, and the acrylic polymer particles have an average particle size (D50) of 200 nm to 700 nm.
6. 2. The separator for an electrochemical device according to claim 1, wherein a mixing ratio by weight of the hybrid polymer particles and the acrylic polymer particles is in the range of 8:2 to 2:
8.
7. 2. The separator for an electrochemical device according to claim 1, wherein the Tg of the acrylic polymer contained in the hybrid polymer particles is at least 10[deg.] C. lower than the Tg of the acrylic polymer contained in the acrylic polymer particles.
8. 8. The separator for electrochemical devices according to claim 7, wherein the acrylic polymer contained in the hybrid polymer particles has a Tg of 10° C. to 30° C., and the acrylic polymer contained in the acrylic polymer particles has a Tg of 30° C. to 50° C.
9. 2. The separator for an electrochemical device according to claim 1, wherein the fluorine-based polymer is a homopolymer of vinylidene fluoride, a copolymer of vinylidene fluoride and another polymerizable monomer, or a mixture of two or more of them.
10. 10. The separator for an electrochemical device according to claim 9, wherein the monomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2-difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3 dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride.
11. 10. The separator for an electrochemical device according to claim 9, wherein the fluorine-based polymer is a copolymer of vinylidene fluoride and hexafluoropropylene.
12. 10. The separator for an electrochemical device according to claim 9, wherein the content of the monomer is 1% by weight to 20% by weight of the copolymer.
13. 2. The separator for electrochemical devices according to claim 1, wherein the acrylic polymer constituting the hybrid polymer particles and the acrylic polymer constituting the acrylic polymer particles each independently contain an alkyl (meth)acrylate repeating unit having an alkyl group having 1 to 18 carbon atoms.
14. 2. The separator for an electrochemical device according to claim 1, wherein the organic / inorganic composite porous coating layer comprises the particulate binder resin in a range of 1 wt % to 30 wt % of the organic / inorganic composite porous coating layer.
15. 2. The separator for an electrochemical device according to claim 1, wherein the inorganic particles have an average particle size (D50) in the range of 200 nm to 3 μm.
16. 2. The separator for electrochemical devices according to claim 1, wherein the organic / inorganic composite porous coating layer is formed by coating a slurry in which the particulate binder resin and inorganic particles are dispersed in an aqueous dispersion medium on at least one surface of a porous polymer substrate, and then drying the slurry.
17. An electrochemical element comprising a negative electrode, a positive electrode, and a separator interposed between the negative electrode and the positive electrode, 17. An electrochemical device, comprising the separation membrane according to claim 1.
18. The electrochemical device according to claim 17, wherein the electrochemical device is a lithium secondary battery.
Citation Information
Patent Citations
Heat-resistant diaphragm as well as preparation method and application thereof
CN114335903A
Electrode coated with porous active layer, manufacturing method thereof, and electrochemical device provided with same
JP2009529762A
Separator and method of manufacturing the same, and lithium secondary battery including the separator
JP2013235824A
Separator for lithium secondary battery and a method of making the same
KR1020160118979A
Separator for rechargeable battery and rechargeable battery including the same
KR1020180063649A